High-solid low-viscosity light-cured alumina matrix ceramic slurry and preparation method thereof
By introducing SIC powder and nano -silicon carbide particles in the ceramic slurry of alumina substrate to optimize the use and dispersion of ceramic particles, solve the problem of low mechanical properties of aluminum oxide matte ceramic slurry parts, realized Preparation of ceramic parts with high density and high -mechanical properties.
Patent Information
- Application Number
- CN202411102047.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-08-12
AI Technical Summary
After 3D printing of existing alumina matrix ceramic slurries, the mechanical properties of the parts are not high, making it difficult to meet the requirements of complex structures and high density.
Adopt high -solid and low -viscosity optical aluminum aluminum -based ceramic slurry. By adjusting the composition and proportion of the ceramic group and the polymer group, increase the addition of SIC powder and nano -silicon carbide particles to optimize the particle size level of ceramic particles The use of and dispersant use, improve the solid -liquid compatibility and mechanical properties of the slurry.
It significantly improves the mechanical properties and density of ceramic parts, reduces the viscosity and settlement of the slurry, and enhances the abrasion resistance and compressiveness of the printed parts.
Smart Images

Figure CN119371192A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photocurable 3D printing materials, and in particular to a high-solid and low-viscosity photocurable alumina matrix ceramic slurry and a preparation method thereof. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] 3D printing, also known as additive manufacturing technology, has unique advantages in manufacturing parts with complex structures and geometric shapes. Additive manufacturing of ceramic parts with complex structures and high mechanical properties has also become a hot research direction at home and abroad in recent years. Ceramic slurry needs to increase the solid content in the slurry as much as possible while maintaining good rheological properties, stability and dispersibility to improve the density and mechanical properties of printed parts.
[0004] However, due to the material properties of alumina itself, the mechanical properties of the parts printed by alumina-based ceramic slurry are not high. Therefore, it is necessary to provide a light-cured ceramic slurry to improve the mechanical properties of the parts printed by alumina-based ceramic slurry. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-solid and low-viscosity photocurable alumina-based ceramic slurry, which has good rheology and stability. By adjusting the ceramic components and polymer components of the slurry system, the solid content, viscosity and stability of the slurry are regulated at the same time. In addition, by adding nano-silicon carbide particles and silicon carbide whiskers, the printed parts are subjected to nano-phase toughening and whisker toughening. The present invention also provides a method for preparing a high-solid and low-viscosity photocurable alumina-based ceramic slurry.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] In the first aspect, a high-solid, low-viscosity photocurable alumina-based ceramic slurry is composed of the following raw materials, measured by weight percentage: 32-38% photocurable resin, 1.5-2.5% photoinitiator, 2.5-3.5% dispersant, and the balance is ceramic particle powder;
[0008] The ceramic particle powder includes Al2O3 powder and SiC powder, the mass of SiC powder is 0.1-20% of the total mass of the ceramic particle powder, the ceramic particle powder is graded by large particle size, medium particle size and small particle size, the large particle size is 1.5-2.5 μm, the medium particle size is 0.35-0.45 μm, and the small particle size is 0.05-0.15 μm, and the dispersant is one or more of silane coupling agent KH-550, silane coupling agent KH-560, rheological additive BYK-410 and stearic acid SA.
[0009] The present invention selects silane coupling agent KH-550, silane coupling agent KH-560, rheological additive BYK-410 and stearic acid SA as dispersants, which can adsorb long chains of dispersant functional groups on the surface of ceramic particle powder to form steric stabilization between particles, thereby effectively improving the stability and dispersion degree of ceramic slurry and further reducing the shear viscosity of the slurry.
[0010] The present invention optimizes the distribution of ceramic particles by using three-level particle size ratios of ceramic particle powder (wherein, large-size and medium-size ceramic particle powders are Al2O3 powders, and small-size ceramic particle powders are Al2O3 powders or nano-silicon carbide particles), and adds SiC powder (especially nano-silicon carbide particles and / or silicon carbide whiskers) as an additive phase to the ceramic component to reduce the viscosity of the slurry and improve the mechanical properties of the ceramic sintering.
[0011] On the other hand, a method for preparing the above-mentioned high-solid and low-viscosity photocurable alumina matrix ceramic slurry comprises modifying the ceramic particle powder with a dispersant so that the ceramic particle powder adsorbs the long functional group chain of the dispersant to obtain modified ceramic particle powder; and uniformly mixing the modified ceramic particle powder with a photocurable resin and a photoinitiator to obtain the obtained product.
[0012] The present invention firstly uses a dispersant to modify the ceramic particle powder, and the hydroxyl groups on the surface of the ceramic particle powder are physically adsorbed with one end of the dispersant, so that the hydrophobic long chains in the dispersant are freed, thereby increasing the compatibility of the ceramic particle powder with organic matter. At the same time, the surface of the modified ceramic particle powder contains free hydrophobic long chains, which can play a steric hindrance role, making it more dispersed and stable in the photocurable resin, improving the solid-liquid compatibility of the ceramic slurry, and facilitating the preparation of high-performance ceramic slurry.
[0013] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0014] Since carbide ceramics have the characteristics of low density, low thermal expansion coefficient, high thermal conductivity and high rigidity, the present invention adds SiC powder as a reinforcing phase to the ceramic slurry. While maintaining the original excellent performance of the alumina-based slurry, high-quality, high-rigidity ceramic parts are prepared. The present invention adjusts the composition and ratio of the ceramic components and polymer components in the ceramic slurry to improve the solid-liquid compatibility in the slurry system and optimizes the accumulation of solid ceramic particles in the slurry, thereby configuring an alumina-based slurry with high solid phase content, low viscosity and good stability. At the same time, silicon carbide whiskers and nano-silicon carbide particles are introduced as added phases, and the mechanical properties of the components printed out by the subsequent slurry are improved through whisker toughening and nano-phase toughening. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0016] Figure 1 is the sedimentation diagram of the slurry with silicon carbide whiskers added in Example 1;
[0017] Figure 2 This is a shear viscosity diagram of the slurry with silicon carbide whiskers added to Example 1;
[0018] Figure 3 This is a performance diagram of the slurry with different dispersants added to Example 2 and Comparative Example 1, where: Figure 3 (a) is the slurry sedimentation diagram. Figure 3 (b) is the shear viscosity diagram of the slurry;
[0019] Figure 4 The contact angle test diagram of the modified powders with different dispersants added to Example 2 and Comparative Example 1;
[0020] Figure 5 The scanning electron microscope images of the modified powders of Example 2 and Comparative Example 1 with different dispersants added are shown in FIG. Figure 5 (a) is unmodified powder, (b) is KH560 modified powder, (c) is BYK410 modified powder, and (d) is SA modified powder;
[0021] Figure 6 This is the shear viscosity diagram of the slurry with silicon carbide particles added to Example 3. DETAILED DESCRIPTION
[0022] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0023] The development and research of ceramic slurry systems based on photocuring 3D printing technology is of great significance for broadening the application scope of photocuring technology and promoting the development of photocuring technology. With the development of photocuring additive manufacturing technology, more ceramic material systems and structures can be realized through 3D printing. The existing alumina-based ceramic slurry has good rheological properties and excellent printing performance, but the mechanical properties of the parts after molding need to be improved. Therefore, the present invention provides a high-solid and low-viscosity photocuring alumina matrix ceramic slurry and a preparation method thereof.
[0024] A typical embodiment of the present invention provides a high-solid and low-viscosity photocurable alumina-based ceramic slurry, which is composed of the following raw materials in terms of mass percentage: 32-38% photocurable resin, 1.5-2.5% photoinitiator, 2.5-3.5% dispersant, and the balance is ceramic particle powder;
[0025] The ceramic particle powder includes Al2O3 powder and SiC powder, the mass of SiC powder is 0.1-20% of the total mass of the ceramic particle powder, the ceramic particle powder is graded by large particle size, medium particle size and small particle size, the large particle size is 1.5-2.5 μm, the medium particle size is 0.35-0.45 μm, and the small particle size is 0.05-0.15 μm, and the dispersant is one or more of silane coupling agent KH-550, silane coupling agent KH-560, silane coupling agent BYK-410 and stearic acid SA.
[0026] The ceramic particle powder in the slurry adopts a three-level particle gradation (wherein the large-size and medium-size ceramic particle powders are Al2O3 powders, and the small-size ceramic particle powders are Al2O3 powders or nano-silicon carbide particles), so that the small-size ceramic powder can be fully filled into the gaps of the large-size ceramics, ensuring that the sintered alumina matrix ceramics have a high density. At the same time, the particle gradation can maximize the solid phase content of the slurry and ensure the mechanical properties of the sintered ceramics; at the same time, SiC powder (especially nano-silicon carbide particles and / or silicon carbide whiskers) is added to the ceramic component as an additive phase to reduce the viscosity of the slurry and improve the mechanical properties of the sintered ceramics.
[0027] In some embodiments, the large particle size is 1.8 to 2.2 μm, preferably 1.9 to 2.1 μm.
[0028] In some embodiments, the median particle size is 0.37 to 0.43 μm, preferably 0.39 to 0.41 μm.
[0029] In some embodiments, the small particle size is 0.07 to 0.13 μm, preferably 0.09 to 0.11 μm.
[0030] In some embodiments, the SiC powder is silicon carbide whiskers (SiC w ) and / or SiC nanoparticles. The silicon carbide whisker has a diameter of 0.1 to 0.4 μm and a length of 5 to 15 μm (preferably 8 to 12 μm). The particle size of the SiC nanoparticles is 0.05 to 0.1 μm.
[0031] In some embodiments, the photocurable resin is acrylate monomers HDDA (1,6-hexanediol diacrylate) and TMPTA (trimethylolpropane triacrylate).
[0032] In some embodiments, the photoinitiator is 1,1-dimethoxy-1-phenylacetophenone PI651.
[0033] In some embodiments, the ceramic slurry has a viscosity of 1-5 Pa·s.
[0034] Another embodiment of the present invention provides a method for preparing the above-mentioned high-solid and low-viscosity photocurable alumina matrix ceramic slurry, wherein the ceramic particle powder is modified by a dispersant so that the ceramic particle powder adsorbs the long functional group chain of the dispersant to obtain modified ceramic particle powder; the modified ceramic particle powder is evenly mixed with a photocurable resin and a photoinitiator to obtain.
[0035] The preparation method of the ceramic slurry effectively improves the effect of ceramic powder modification, and the obtained ceramic slurry has higher stability and better solid-liquid compatibility, while reducing the sedimentation caused by excessive modifiers. The obtained high-solid and low-viscosity light-cured alumina-based ceramic slurry has good rheological properties, effectively improving the solid-liquid compatibility and stability of the slurry while reducing the viscosity of the slurry.
[0036] The ceramic particle powder adsorption of the present invention is prepared by physical adsorption; in some embodiments, the modification process is: adding the ceramic particle powder and the dispersant into a solvent and ultrasonically dispersing them to obtain the ceramic particle powder.
[0037] In one or more embodiments, the ceramic particle powder is first dried and then added to a solvent with a dispersant for ultrasonic dispersion. Specifically, the first drying is vacuum drying. More specifically, the temperature of the first drying is 110 to 130° C., and the drying is performed for 10 to 15 hours. More specifically, the heating rate of the first drying is 0.1 to 3° C. / min. The drying effect is better under this condition.
[0038] In one or more embodiments, the second drying is performed after ultrasonic dispersion. Specifically, the second drying is vacuum drying. More specifically, the temperature of the second drying is 110-130° C., and the time is 10-15 hours. More specifically, the heating rate of the second drying is 0.1-3° C. / min. The drying effect under this condition is better.
[0039] In one or more embodiments, the solvent is a mixed solution of ethanol and water. Specifically, the mass ratio of ethanol to water is any ratio, preferably 8.5-9.5:1.5-0.5.
[0040] In one or more embodiments, the ultrasonic dispersion temperature is room temperature. The room temperature described in the present invention refers to the temperature of the indoor environment, which is generally 15-30°C.
[0041] In some embodiments, a photocurable resin and a photoinitiator are mixed uniformly to obtain a liquid phase portion of a ceramic slurry, and then the modified ceramic particle powder is added to the liquid phase portion of the ceramic slurry and mixed uniformly.
[0042] In one or more embodiments, the mixing temperature of the photocurable resin and the photoinitiator is 30-40° C. and the mixing time is 25-35 min. Under this condition, the mixing is more uniform.
[0043] In one or more embodiments, the method of mixing the liquid phase of the ceramic slurry with the modified ceramic powder is wet ball milling. Specifically, in the wet ball milling, the material-ball ratio is 1:4-6, the ball milling time is 7-9 hours, and the rotation speed is 150-200 r / min. Specifically, in the wet ball milling, the ball milling balls used are zirconia ball milling balls.
[0044] The following is a further description of the implementation of the present invention in terms of multiple embodiments.
[0045] Example 1
[0046] A photocurable ceramic slurry and a preparation method thereof. The photocurable ceramic slurry is composed of raw materials in the mass ratio shown in Table 1.
[0047] Table 1 Example 1 Ceramic slurry ceramic powder gradation composition
[0048] Group <![CDATA[2μm Al2O3]]> <![CDATA[0.4μm Al2O3]]> <![CDATA[0.1μm Al2O3]]> <![CDATA[0.1μm SiC w ]]> SW-1 50wt% 33.33wt% 8.33wt% 8.33wt% SW-2 50wt% 33.33wt% 12.5wt% 4.17wt% SW-3 50wt% 33.33wt% 4.17wt% 12.5wt% SW-4 50wt% 25wt% 16.67wt% 8.3wt% SW-5 50wt% 33.33wt% - 16.67wt% SW-6 50wt% 25wt% - 25wt% SW-7 40wt% 30wt% - 30wt%
[0049] The preparation process of light-cured ceramic slurry is as follows:
[0050] According to different mass ratios, corresponding mass fractions of silicon carbide whiskers are weighed to obtain mixed ceramic powders. Subsequently, the mixed ceramic powders are modified using a dispersant KH560 to obtain the ceramic component part of the ceramic slurry. The photocurable resins HDDA (1,6-hexanediol diacrylate) and TMPTA (trimethylolpropane triacrylate) are mixed with a photoinitiator 2,2-dimethoxy-2-phenylacetophenone (PI651) to obtain the liquid phase of the ceramic slurry, which is then mixed with the modified ceramic powder to obtain the ceramic slurry. The modification process includes drying the mixed powder, ultrasonic dispersion and drying the modified powder. The drying conditions are: vacuum drying; heating to 120°C at a heating rate not higher than 3°C / min; drying for 12h. The solvent for ultrasonic dispersion includes an ethanol / water mixture with a mass ratio of 9:1. The ultrasonic dispersion includes: ultrasonically dispersing the dried ceramic powder, the dispersant and the solvent at room temperature for 1h. The method of mixing the photocurable resin and the photoinitiator includes: magnetically stirring the resin and the photoinitiator for 30 minutes under a 35°C water bath heating condition to obtain a liquid phase of the ceramic slurry. The method of mixing the liquid phase of the ceramic slurry with the modified ceramic powder is wet ball milling. The ball milling balls of the wet ball milling are zirconium oxide ball milling balls, the material-to-ball ratio is 1:5, the ball milling time is 8 hours, and the rotation speed is 180r / min.
[0051] Example 2
[0052] A photocurable photocurable ceramic slurry and a preparation method thereof. The photocurable ceramic slurry is composed of the raw materials shown in Table 2.
[0053] Table 2 Composition of light-cured ceramic slurry in Example 2
[0054] Group Dispersants Prepolymer Ceramic powder f1 KH560 HDDA+TMPTA Al2O3+SiC
[0055] The ceramic powder is composed of three particle sizes: coarse, medium and fine. The coarse particle powder is 2μm alumina powder, the medium particle is 0.4μm alumina powder, and the fine particle is 0.1μm silicon carbide nanoparticles, with a mass ratio of 5:3:2. The mass ratio of the dispersant is 4%, the mass ratio of the prepolymer is 36%, and the mass ratio of the ceramic powder is 60%.
[0056] The preparation process of light-cured ceramic slurry is as follows:
[0057] Alumina ceramic powder of corresponding mass fraction is weighed according to the mass ratio to obtain mixed ceramic powder. Subsequently, the mixed ceramic powder is modified with dispersant KH560 to obtain the ceramic component part of the ceramic slurry. The photocurable resin HDDA (1,6-hexanediol diacrylate) and TMPTA (trimethylolpropane triacrylate) are mixed with the photoinitiator 2,2-dimethoxy-2-phenylacetophenone (PI651) to obtain the liquid phase of the ceramic slurry, which is then mixed with the modified ceramic powder to obtain the ceramic slurry. The modification process includes drying the mixed powder, ultrasonic dispersion and drying the modified powder. The drying conditions are: vacuum drying; heating to 120°C at a heating rate of 3°C / min; drying for 12h. The solvent for ultrasonic dispersion includes an ethanol / water mixture with a mass ratio of 9:1. The ultrasonic dispersion includes: ultrasonically dispersing the dried ceramic powder, the dispersant and the solvent at room temperature for 1h. The method of mixing the photocurable resin and the photoinitiator includes: magnetically stirring the resin and the photoinitiator for 30 minutes under a 35°C water bath heating condition to obtain a liquid phase of the ceramic slurry. The method of mixing the liquid phase of the ceramic slurry with the modified ceramic powder is wet ball milling. The ball milling balls of the wet ball milling are zirconium oxide ball milling balls, the material-to-ball ratio is 1:5, the ball milling time is 8 hours, and the rotation speed is 180r / min.
[0058] Example 3
[0059] A photocurable ceramic slurry and a preparation method thereof. The photocurable ceramic slurry is composed of raw materials in the mass ratio shown in Table 3.
[0060] Table 3 Example 3 Ceramic slurry ceramic powder gradation composition
[0061] Group <![CDATA[2μm Al2O3]]> <![CDATA[0.4μm Al2O3]]> 0.05-0.1μm SiC S-1 50wt% 33.33wt% 16.67wt% S-2 50wt% 25wt% 25wt% S-3 60wt% 30wt% 10wt% S-4 50wt% 40wt% 10wt% S-5 60wt% 20wt% 20wt%
[0062] The preparation process of light-cured ceramic slurry is as follows:
[0063] According to different mass ratios, corresponding mass fractions of silicon carbide nanoparticles are weighed to obtain mixed ceramic powders. Subsequently, the mixed ceramic powders are modified using a dispersant KH560 to obtain the ceramic component part of the ceramic slurry. The photocurable resins HDDA (1,6-hexanediol diacrylate) and TMPTA (trimethylolpropane triacrylate) are mixed with a photoinitiator 2,2-dimethoxy-2-phenylacetophenone (PI651) to obtain the liquid phase of the ceramic slurry, which is then mixed with the modified ceramic powder to obtain the ceramic slurry. The modification process includes drying the mixed powder, ultrasonic dispersion and drying the modified powder. The drying conditions are: vacuum drying; heating to 120°C at a heating rate of 3°C / min; drying for 12h. The solvent for ultrasonic dispersion includes an ethanol / water mixture with a mass ratio of 9:1. The ultrasonic dispersion includes: ultrasonically dispersing the dried ceramic powder, the dispersant and the solvent at room temperature for 1h. The method of mixing the photocurable resin and the photoinitiator includes: magnetically stirring the resin and the photoinitiator for 30 minutes under a 35°C water bath heating condition to obtain a liquid phase of the ceramic slurry. The method of mixing the liquid phase of the ceramic slurry with the modified ceramic powder is wet ball milling. The ball milling balls of the wet ball milling are zirconium oxide ball milling balls, the material-to-ball ratio is 1:5, the ball milling time is 8 hours, and the rotation speed is 180r / min.
[0064] In order to highlight the beneficial effects of the present invention, the following comparative examples are provided.
[0065] Comparative Example 1
[0066] A photocurable photocurable ceramic slurry and a preparation method thereof. The photocurable ceramic slurry is composed of the raw materials shown in Table 3.
[0067] Table 4 Comparative Example 1 Photocurable Ceramic Slurry Composition
[0068] Group Dispersants Prepolymer Ceramic powder f0 - HDDA+TMPTA <![CDATA[Al2O3+SiC]]> f2 SA HDDA+TMPTA <![CDATA[Al2O3+SiC]]> f3 BYK410 HDDA+TMPTA <![CDATA[Al2O3+SiC]]>
[0069] The ceramic powder is composed of three particle sizes: coarse, medium and fine. The coarse particle powder is 2μm alumina powder, the medium particle is 0.4μm alumina powder, and the fine particle size is 0.1μm silicon carbide nanoparticles, with a mass ratio of 5:3:2. The mass ratio of the dispersant is 4%, the mass ratio of the prepolymer is 36%, and the mass ratio of the ceramic powder is 60%.
[0070] The preparation process of light-cured ceramic slurry is as follows:
[0071] Alumina ceramic powder of corresponding mass fraction is weighed according to the mass ratio to obtain mixed ceramic powder. The mixed ceramic powder is then modified with a dispersant to obtain the ceramic component part of the ceramic slurry. The photocurable resin HDDA (1,6-hexanediol diacrylate) and TMPTA (trimethylolpropane triacrylate) are mixed with the photoinitiator 2,2-dimethoxy-2-phenylacetophenone (PI651) to obtain the liquid phase of the ceramic slurry, which is then mixed with the modified ceramic powder to obtain the ceramic slurry. The modification process includes drying the mixed powder, ultrasonic dispersion and drying the modified powder. The drying conditions are: vacuum drying; heating to 120°C at a heating rate of 3°C / min; drying for 12h. The solvent for ultrasonic dispersion includes an ethanol / water mixture with a mass ratio of 9:1. The ultrasonic dispersion includes: ultrasonically dispersing the dried ceramic powder, the dispersant and the solvent at room temperature for 1h. The method of mixing the photocurable resin and the photoinitiator includes: magnetically stirring the resin and the photoinitiator for 30 minutes under a 35°C water bath heating condition to obtain a liquid phase of the ceramic slurry. The method of mixing the liquid phase of the ceramic slurry with the modified ceramic powder is wet ball milling. The ball milling balls of the wet ball milling are zirconium oxide ball milling balls, the material-to-ball ratio is 1:5, the ball milling time is 8 hours, and the rotation speed is 180r / min.
[0072] Effect test
[0073] In order to verify the performance of the photocurable ceramic slurry and the photocurable ceramic prepared by the present invention, the present invention also provides an effect test.
[0074] The ceramic slurry in Example 1 was subjected to sedimentation experiment and viscosity test, see Figure 1 and Figure 2 , Figure 1 is the sedimentation curve of the ceramic slurry prepared in Example 1 of the present invention, Figure 2 : is the viscosity curve of the ceramic slurry obtained in Example 1 of the present invention. Figure 1 It can be seen that with the increase of silicon carbide whisker content, the slurry sedimentation rate becomes faster, but it is not less than 85%. This may be because silicon carbide whiskers are long rods, which easily cause ceramic particles to agglomerate and settle. Figure 2 It can be seen that with the increase of silicon carbide whisker content, the viscosity also increases, but at a shear rate of 30s -1 When the slurry is stirred for 2 hours, the viscosity of the slurry is no higher than 3Pa·s.
[0075] The ceramic slurries in Example 2 and Comparative Example 1 were subjected to sedimentation experiments and viscosity tests. Figure 3 , Figure 3 This is a graph showing the performance of the slurry with different dispersants added to Example 1 of Example 2. Figure 3 (a) It can be seen that for ceramic slurries with high solid content, the effect of dispersants in improving slurry viscosity is more obvious, among which KH560 in Example 2 has the best effect. Figure 3 (b) It can be seen that the three dispersants can play a certain role in the sedimentation of the ceramic slurry. The ceramic slurry modified by Example 2 can maintain less sedimentation at a lower viscosity and is the best choice for modified alumina-based ceramic slurry.
[0076] In order to further confirm the modification effect of the dispersant on the ceramic powder, the modified powder in the ceramic slurry of Example 2 and Comparative Example 1 was pressed into tablets, and the contact angle with the trifunctional resin TMPTA was measured. The contact angle was used to characterize the compatibility of the two phases. The larger the contact angle, the smaller the compatibility of the two phases. The results are shown in FIG. Figure 4 As shown in the figure, the better the solid-liquid compatibility of the ceramic slurry, the more dispersed and stable the ceramic powder is in the liquid phase, and it is not easy to produce particle agglomeration and sedimentation. Figure 4 It can be seen that the KH560 modified powder has the smallest contact angle with TMPTA, so the prepared ceramic slurry has excellent stability, and the particle agglomeration and sedimentation in the slurry are relatively light. The low sedimentation rate of the SA modified slurry in Comparative Example 1 is mainly due to the high viscosity of the slurry, which makes it difficult for the solid phase to settle, and it is not a manifestation of good dispersion effect. The KH560 in Example 2 has the best effect on improving the solid-liquid compatibility of the ceramic slurry.
[0077] The morphology of the modified powder in the ceramic slurry of Example 2 and Comparative Example 1 was characterized by scanning electron microscopy. Figure 5 , Figure 5 The scanning electron microscope images of the modified powders of Example 2 and Comparative Example 1 with different dispersants added are shown in FIG. Figure 5 (a) is unmodified powder, (b) is KH560 modified powder, (c) is BYK410 modified powder, and (d) is SA modified powder. It can be seen from the figure that the unmodified powder in Comparative Example 1 is seriously agglomerated, and alumina powders of different particle sizes agglomerate together to form agglomerates. The ceramic powders modified by BYK410 and SA in Comparative Example 1 are also relatively dispersed, but the adsorption effect on the particle surface is not as good as that of KH560. The modified powder in Example 2 is more dispersed, and there is an adsorption modifier on the particle surface.
[0078] The viscosity of the ceramic slurry in Example 3 was tested. Figure 6 , Figure 6 : is the viscosity curve of the ceramic slurry obtained in Example 3 of the present invention. Figure 6 It can be seen that all five groups of slurries showed obvious shear thinning, which is beneficial to the leveling of the slurry during printing. With the increase of the content of 0.05-0.1μm small-size SiC particles, the slurry viscosity showed an upward trend, but at a shear rate of 30s -1 When the slurry is added with silicon carbide whiskers, the viscosity of the slurry is not higher than 3Pa·s. The slurry has the same excellent rheological properties as the slurry added with silicon carbide whiskers in Example 1.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-solid and low-viscosity photocurable alumina-based ceramic slurry, characterized in that: The composition is composed of the following raw materials in terms of mass percentage: 32-38% of photocurable resin, 1.5-2.5% of photoinitiator, 2.5-3.5% of dispersant, and the balance is ceramic particle powder; The ceramic particle powder includes Al2O3 powder and SiC powder, the mass of SiC powder is 0.1-20% of the total mass of the ceramic particle powder, the ceramic particle powder is graded by large particle size, medium particle size and small particle size, the large particle size is 1.5-2.5 μm, the medium particle size is 0.35-0.45 μm, and the small particle size is 0.05-0.15 μm, and the dispersant is one or more of silane coupling agent KH-550, silane coupling agent KH-560, silane coupling agent BYK-410 and stearic acid SA.
2. The high-solid and low-viscosity photocurable alumina-based ceramic slurry according to claim 1, characterized in that: The maximum particle size is 1.8-2.2 μm, or 1.9-2.1 μm; Or, the median particle size is 0.37 to 0.43 μm, or 0.39 to 0.41 μm; Alternatively, the small particle size is 0.07 to 0.13 μm, or 0.09 to 0.11 μm.
3. The high-solid and low-viscosity photocured alumina-based ceramic slurry according to claim 1, characterized in that: The SiC powder is silicon carbide whiskers and / or SiC nanoparticles; or, the silicon carbide whiskers have a diameter of 0.1 to 0.4 μm and a length of 5 to 15 μm, or 8 to 12 μm; or, the SiC nanoparticles have a particle size of 0.05 to 0.1 μm.
4. The high-solid and low-viscosity photocurable alumina-based ceramic slurry according to claim 1, characterized in that: The photocurable resin is 1,6-hexanediol diacrylate and trimethylolpropane triacrylate; Alternatively, the photoinitiator is 1,1-dimethoxy-1-phenylacetophenone.
5. The high-solid and low-viscosity photocurable alumina-based ceramic slurry according to claim 1, characterized in that: The viscosity of the ceramic slurry is 1-5 Pa·s.
6. A method for preparing the high-solid and low-viscosity photocurable alumina-based ceramic slurry according to claim 1, characterized in that: The ceramic particle powder is modified by using a dispersant so that the ceramic particle powder absorbs the long functional group chain of the dispersant to obtain modified ceramic particle powder; the modified ceramic particle powder is evenly mixed with a photocurable resin and a photoinitiator to obtain the obtained product.
7. The method for preparing the high-solid and low-viscosity photocurable alumina-based ceramic slurry according to claim 6, characterized in that: The modification process is as follows: ceramic particle powder and a dispersant are added into a solvent and ultrasonically dispersed to obtain the product.
8. The method for preparing the high-solid and low-viscosity photocurable alumina-based ceramic slurry according to claim 7, characterized in that: The ceramic particle powder is first dried, and then added to a solvent with a dispersant for ultrasonic dispersion; or, the first drying is vacuum drying; or, the temperature of the first drying is 110 to 130° C., and the time is 10 to 15 hours; or, the heating rate of the first drying is 0.1 to 3° C. / min; Or, the second drying is performed after ultrasonic dispersion; or, the second drying is vacuum drying; or, the temperature of the second drying is 110-130° C., and the time is 10-15 h; or, the heating rate of the second drying is 0.1-3° C. / min; Or, the solvent is a mixed solution of ethanol and water; or, the mass ratio of ethanol to water is 8.5-9.5:1.5-0.
5.
9. The method for preparing the high-solid and low-viscosity photocurable alumina-based ceramic slurry according to claim 6, characterized in that: The photocurable resin and the photoinitiator are mixed uniformly to obtain the liquid phase part of the ceramic slurry, and then the modified ceramic particle powder is added to the liquid phase part of the ceramic slurry and mixed uniformly.
10. The method for preparing the high-solid and low-viscosity light-cured alumina-based ceramic slurry according to claim 9, characterized in that: The mixing temperature of the photocurable resin and the photoinitiator is 30-40°C, and the mixing time is 25-35 minutes; Or, the method of mixing the liquid phase of the ceramic slurry with the modified ceramic powder is wet ball milling; or, in wet ball milling, the material-ball ratio is 1:4-6, the ball milling time is 7-9h, and the rotation speed is 150-200r / min; or, in wet ball milling, the ball milling balls used are zirconia ball milling balls.
Citation Information
Patent Citations
Inorganic nanocomposite material for 3D (three-dimensional) printing and preparation method thereof
CN104478441A
Silicon carbide / alumina ceramic composite photosensitive paste material for SLA-3D printing and preparation method thereof
CN109851327A
Wear-resistant and high-temperature-resistant numerical control cutter material based on 3D printing and preparation method thereof
CN111151761A
Graphene ceramic composite material prepared based on 3D printing and preparation method thereof
CN112125653A
Preparation method of high-solid low-viscosity photocuring ceramic slurry
CN118184320A